The Titanic: an interactive history adventure - Temple, Bob. (Mankato, MN Capstone Press, 2008)
Describes the events surrounding the sinking of the ship Titanic in 1912. The reader's choices reveal the historical details from the perspective of a first-class passenger, a third-class passenger, and a crewmember.
5 - 9
Keywords: Titanic (Steamship).; Shipwrecks - North Atlantic Ocean